2007
DOI: 10.1186/1471-2148-7-186
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and domestication of Indian river buffalo

Abstract: BackgroundThe water buffalo- Bubalus bubalis holds tremendous potential in livestock sector in many Asian countries, particularly India. The origin, domestication and genetic structure of the Indian river buffalo are poorly understood. Therefore, to understand the relationship among the maternal lineages of Indian river buffalo breeds and their domestication process, we analysed mitochondrial D-loop region of 217 animals representing eight breeds from eight different locations in India along with published seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 20 publications
4
68
3
Order By: Relevance
“…Three population genetic studies of modern water buffalo (Kierstein et al, 2004, Kumar et al, 2007a,b, Lau et al, 1998 point to different regions in south Asia or SE Asia as the origin of domestication of water buffalo. The exclusion of China as a domestication center could potentially be due to a sampling bias, as none of the studies incorporated DNA samples from modern Chinese water buffalo.…”
Section: Implications For Domestication History Of Modern Water Buffamentioning
confidence: 98%
“…Three population genetic studies of modern water buffalo (Kierstein et al, 2004, Kumar et al, 2007a,b, Lau et al, 1998 point to different regions in south Asia or SE Asia as the origin of domestication of water buffalo. The exclusion of China as a domestication center could potentially be due to a sampling bias, as none of the studies incorporated DNA samples from modern Chinese water buffalo.…”
Section: Implications For Domestication History Of Modern Water Buffamentioning
confidence: 98%
“…The river buffalo has many uses but is mainly used in the dairy industry in comparison to the swamp buffalo which is more commonly used for meat and as a working animal [2]. The areas in which the two types are distributed also differ slightly as the river buffalo is more commonly situated in the Caribbean, Africa, Indian sub-continent, Mediterranean regions, and South America, in comparison to the swamp buffalo which is predominantly found in South-East Asia and China [3]. The reproductive abilities of the water buffalo have become increasingly important, and a point of concern, due to its many roles throughout the world *Address correspondence to this author at the School of Veterinary Medicine and Science, Faculty of Medicine, University of Nottingham, College Road, Sutton Bonington, Leicestershire, LE12 5RD, England, UK; Tel: +44 (0)7780701710; Fax: +44 (0)7780701710 E-mail: elgendyanatomist@yahoo.com, catrin.rutland@nottingham.ac.uk and its economic importance.…”
Section: Introductionmentioning
confidence: 99%
“…This study also concluded that the increment of flow does not occur and stabilized after it reaches the ratio of maximum valve lift per diameter (L/D) of 0.25. Research by Kumar and Nagarajan [4] also investigated on those non-dimensional parameters with the inclusion of the swirl ratio analysis. Analysis showed the correlation of the obtained data from the flow bench test and also from the modelling by the commercial CFD code.…”
Section: Introductionmentioning
confidence: 99%
“…This research discussed on the swirl improvement by modification of the valve design. Kumar and Nagarajan [4] defined that valve shrouding and twisted tape insert can improve the swirl in engine. From the research, it was also concluded that although flow increased along the valve lift, this took a penalty on the increased friction.…”
Section: Introductionmentioning
confidence: 99%